Analysis of the elite athletes' somatotypes - Rakovic, A.; Savanovic, V.; Stankovic, D.; Pavlovic, R.; Simeonov, A.; Petkovic, E. (Acta Kinesiologica, 2015)
In many sports somatotype components are not homogeneous, not even in the groups that were singled out by the quality. There were significant differences within the same sport and in terms of the playing position. This is especially reflected in ball sports, team sports, while in individual groups somatotypes were becoming more homogeneous as a higher level of athletic performance was reached. In a review of research many comparisons of the somatotype of athletes in various sports were shown, obtained findings indicate the differentiation of sports according to the somatotype, and these findings are important in the selection of talents in the field of professional sports.